Letter to Mayor Jane Tolmach from Antonio Salcedo Sahagun - Antonio Salcedo Sahagun:::::: (1973)
A letter from Antonio Salcedo Sahagun, Municipal President of the city of Ocotlán, Jalisco, Mexico to Mayor Jane Tolmach apologizing for cancelling his visit to the city of Oxnard in 1973.